Parallelized disruption of prokaryotic and eukaryotic cells via miniaturized and automated bead mill. Issue 8 (6th May 2020) - Jansen, Roman P.; Müller, Moritz Fabian; Schröter, Sophie Edith; Kappelmann, Jannick; Klein, Bianca; Oldiges, Marco; Noack, Stephan
Abstract: The application of integrated microbioreactor systems is rapidly becoming of more interest to accelerate strain characterization and bioprocess development. However, available high‐throughput screening capabilities are often limited to target extracellular compounds only. Consequently, there is a great demand for automated technologies allowing for miniaturized and parallel cell disruption providing access to intracellular measurements. In this study, a fully automated bead mill workflow was developed and validated for four different industrial platform organisms: Escherichia coli, Corynebacterium glutamicum, Saccharomyces cerevisiae, and Aspergillus niger . The workflow enables up to 48 parallel cell disruptions in microtiter plates and is applicable at‐line to running lab‐scale cultivations. The resulting cell extracts form the basis for quantitative omics studies where no rapid metabolic quenching is required (e.g., genomics and proteomics).